Taxonomic novelties in Praxelis (Asteraceae, Eupatorieae): a new species and a new combination - Teles, Aristônio M.; Viana, Pedro L.; Esteves, Roberto L. (Phytotaxa, 2016)
A new species, Praxelis minima, is described from the Minas Gerais State, Brazil. It appears to be closely related to P. kleinioides; illustrations, comments, distribution map, and conservation status for the new species are provided. Additionaly a new combination, P. decumbens based on Chromolaena decumbens, is proposed because of its conical receptacle and conspicuously asymmetrical carpopodium. A key to the species of Praxelis occurring in Minas Gerais is provided.